Railway Territories – A Methodological approach to Urban Studies - Isidoro, I.; Marat-Mendes, T.; Vera Regina Tangari (28th International Seminar on Urban Form 2020, 2020)
The main question that shaped this study was how to characterize and map morphological changes occurred in urban areas crossed by railway infrastructures. This paper presents a method to approach these areas, from a morphological perspective. The impact of the relationship between public investment and private interests on land use as strategic agents of territorial and urban transformation areas also here highlighted. The method, applied in a comparative analysis of two suburban railway lines, of different geographical contexts, Lisbon (Portugal) and Rio de Janeiro (Brazil), provides a potential multi-scale morphological analysis, which includes the early development period of railways ( XIXth century) but also the actual times, throughout an evolutive perspective of the transformation stages. As a result, specific morphologic elements are identified, which relate to the combination of factors such as landscape, urban layout, buildings and open spaces, for the characterization of the railway territories. New categories of urban elements, namely: i) spatial implementation of the railway domain, ii) barriers, iii) railway stations, among others, are discussed and presented as important elements to take in account on urban future morphological studies. This paper aims to emphasize the methodological value and furthermore suggests their application on morphological analysis